Understanding the Novel Approach of Nanoferroptosis for Cancer Therapy - Sheikh, Afsana; Kesharwani, Prashant; Almalki, Waleed H.; Almujri, Salem Salman; Dai, Linxin; Chen, Zhe‑Sheng; Sahebkar, Amirhossein; Gao, Fei (Nano-Micro Letters, 2024)
As a new form of regulated cell death, ferroptosis has unraveled the unsolicited theory of intrinsic apoptosis resistance by cancer cells. The molecular mechanism of ferroptosis depends on the induction of oxidative stress through excessive reactive oxygen species accumulation and glutathione depletion to damage the structural integrity of cells. Due to their high loading and structural tunability, nanocarriers can escort the delivery of ferro-therapeutics to the desired site through enhanced permeation or retention effect or by active targeting. This review shed light on the necessity of iron in cancer cell growth and the fascinating features of ferroptosis in regulating the cell cycle and metastasis. Additionally, we discussed the effect of ferroptosis-mediated therapy using nanoplatforms and their chemical basis in overcoming the barriers to cancer therapy. Highlights: 1 Nanoferroptosis: a novel cell death process using various nanoparticles. 2 Therapeutic potential of nanoferroptosis inducers in cancer. 3 Synergistic approach of nanoferroptosis with immunotherapy, sonodynamic and photodynamic therapy.